Manjšinska kinematografija - Šavel-Burkart, Saša (Monitor ISH, 2009)
Young Turkish-German film directors (mostly the third generation of the Turkish minority living in Germany) present stories which are not typically German, crystallising the history and consequences of Turkish migrations to Germany. The theory of film and literature in Germany has recently raised the question whether a text by a German artist with Turkish roots is German or Turkish. As shown by this survey of the history and features of the Turkish- German film, "minority cinema" (a concept based on Deleuze and Guattari's definition of "minority literature") is part of the national culture as well.
Keywords: film; Germany; Nemčija; narodne manjšine; migracije; human migration; nemški film; turški film; jezik; Language; odtujenost; vrednote